The Institutionalization of Spending Review in Budgeting System in Indonesia - Hendi Kristiantoro; Basuki Basuki; Zaenal Fanani (Universitas Muhammadiyah Yogyakarta, Indonesia, 2018)
This research seeks to understand the process of institutionalization of spending review in the budgeting system in Indonesia through the perspective of new institutional theory. Spending review is a method of measuring the quality of government expenditure in the structure of the State Revenue and Expenditure Budget (APBN). This research uses interpretive paradigm based on case study. The results of this study indicate the discovery of symptoms of mimetic isomorphism and coercive isomorphism in the process of institutionalization of spending reviews. The institutionalization process also occurs because of endogenous factors, in which actors within the Directorate General of Treasury reinterpret the effects of foreign elements or recontextualization.